The Effects of Special Education Training on Educator Efficacy in Classroom Management and Inclusive Strategy Use for Students with Autism in Inclusion Classes - Parsons, Lynn D.; Miller, Heather; Deris, Aaron R. (Journal of the American Academy of Special Education Professionals, 2016)
The rise in the number of students with an autism spectrum disorder (ASD) diagnosis combined with the educational trend toward inclusion for students with disabilities has led to an unprecedented number of these students placed in general education classrooms. General educators require appropriate training if these children are to be successful. The problem addressed in the article was that general education teachers have not had sufficient special education training to deal with students with autism. The purpose of the survey was to determine if there was a relationship between special education teacher training and teacher efficacy for both classroom management and inclusion instructional strategies for general educators in a north central Texas school district who work in inclusion classrooms containing students with autism. Study participants included primary and secondary general education teachers in a north central Texas school district who had at least one student with autism in the classroom. Students with autism are participating in inclusive classes at a higher rate than ever before, a situation, which creates new teacher challenges (Kalkbrenner, Braun, Durkin, Maenner, Cunniff, Lee, Pettygrove, Nicholas, & Daniels, 2012). Teachers trained to improve their inclusive teaching efficacy are more likely to use best practices, leading to optimal learner outcomes (Malinen, Savoleinen, & Xu, 2012). Researchers need to identify the best type of teacher training to facilitate inclusion success (Brown & McIntosh, 2012). General education teachers typically do not have adequate special education training to effectively manage the academic and behavioral challenges demonstrated by students with an autism spectrum disorder within the classroom (Killoran et al., 2013, Breitenback, Armstrong, & Bryson, 2013). This lack of training has led to poor teacher efficacy with regards to inclusion strategy implementation and classroom management, which can cause lifelong academic and social failures for these students (Brown & McIntosh, 2012). The purpose of this study was to determine if there was a relationship between the amount of special education training obtained by general educators and their efficacy levels for classroom management and inclusive instructional strategy use with their included students with autism. This study was done to answer two research questions focused on the training levels of general education teachers with students with autism in their classrooms and how training differenced related to efficacy in classroom management and instructional strategy use. RQ1. What is the strength and magnitude of the relationship between efficacy of classroom management and inclusive instructional strategy use as measured by the Teacher Efficacy for Inclusive Practice Scale (TEIP)? RQ2. Is there a main effect of special education training level on classroom management efficacy and inclusive strategy use as measured by the TEIP?